Is tax evasion unethical? / Roshidah Safeei - Safeei, Roshidah (Faculty of Accountancy, 2021)
Taxation is a legal enforcement but there are certain situations in which people evade tax which we call tax evasion. Tax evasion involves efforts by individuals, corporations and other taxpayers to evade taxes by illegal means. For example, taxpayers deliberately misrepresenting or concealing the true state of their affairs to the tax authorities to reduce their tax liability. They declare dishonest tax reporting such as declaring less income, profits or gains or overstating deductions. Normally, taxpayers are trying to minimize their tax payments through legal or illegal means. Tax evasion still happens today due to different views and perceptions of tax evasion. Some people view it as ethical and some people view it as unethical based on their judgment and moral reasoning.